The impact of health literacy on medico‐social follow‐up visits among French cancer survivors 5 years after diagnosis: The national VICAN survey. (23rd April 2020) - Ousseine, Youssoufa M.; Bouhnik, Anne‐Déborah; Peretti‐Watel, Patrick; Sarradon‐Eck, Aline; Memoli, Victoria; Bendiane, Marc‐Karim; Durand, Marie‐Anne; Mancini, Julien
Abstract: Background: Long‐term medico‐social follow‐up of cancer survivors is a challenge because of frequent subsequent troubles. In particular survivors with lower health literacy (HL) have poorer health and might more often use primary care services. However, the impact of HL on cancer survivors' medico‐social follow‐up visits is not known. Our aim was to study medico‐social follow‐up and its associated determinants with a focus on HL 5 years after diagnosis. Methods: VICAN is a national survey of French adult cancer survivors 5 years after a primary cancer. The Single‐Item Literacy Screener was used to define functional HL in this sample. We also asked patients to report the frequency of follow‐up visits with a general practitioner (GP) and/or social worker (SW) regarding their cancer disease. Results: The 4045 participants were 57.4 ± 12.9 years old at diagnosis (range 20‐82) and 1495 (37%) were classified as having inadequate HL. Most cancer survivors (66.7%) were followed up by a GP regarding their cancer while only 14.5% had contact with a SW. After adjustment for sociodemographic, medical, and psychosocial characteristics, medico‐social follow‐ups (GP and SW visits) were more frequent among survivors with low HL. Furthermore, low income, unemployment, impaired mental health, treatment by chemotherapy, and perception of sequelae and fatigue were also associated with more frequent medico‐social follow‐up. Cancer localization association with medico‐social follow‐up was heterogeneous. Conclusion: French cancer survivors with limited HL, lower socioeconomic status, and more severe cancer were more likely to use GP care and social services. Raising awareness and training GPs and SWs on medico‐social follow‐up for patients with limited HL seem necessary to support these vulnerable survivors. Abstract : Among French cancer survivors, 37% had a limited health literacy level. They were more likely to use GP care and social services. Raising awareness and training general practitioners and social workers on medico‐social follow‐up for patients with limited health literacy seem necessary to support these vulnerable survivors.